Design Of A Data Collection System For Waste Collection Officers In Medan Tuntungan District Using Information Technology - Rizky Bukit, Maynaldo; Badawi, Afif; Rosida, Sisi (Cattleya Darmaya Fortuna, 2024)
Development and management of websites (websites) depend on information technology. Websites are digital media that are used for various purposes, such as e-commerce, entertainment, communication, data and information. Companies, schools, colleges, and other organizations have widely used websites for a variety of purposes, including promotions, sales, education, data collection, and other activities that require information to be posted, sent, and received. Medan Tuntungan District, the data collection process for waste collection officers assigned to the District still uses Microsoft Office Excel, where each waste collection officer is assigned to a different location. Data collection on waste collection officers is the process of collecting, processing and recording information relating to individuals on duty or assigned to a sub-district in Medan Tuntungan District. Data collection on waste collection officers is important in maintaining accurate records and appropriate documentation regarding waste collection officers on duty in Medan Tuntungan District.